Curation for a Digital Educational Resources Platform: concepts and practices analyzed and built for a proposal (Research, Society and Development, 2020)
This research aims to propose a digital curation process for Digital Educational Resources platforms. Since, from the critical perspective of technology, we understand that technologies are non-neutral processes, marked by the conceptions and intentionalities of the subjects and institutions that conceive them. Through complex processes of development, validation and evaluation, technological products and contents carry values. Thus, we question ourselves specifically about the processes of evaluation and validation of the contents made available on educational platforms, claiming ways to guarantee a greater participation of the subjects in the decisions about the development of these technologies. To this end, the investigation is based on the theoretical references of critical technology theory and in works in the field of educational technology on digital curation. As a methodological procedure, it was divided into three research phases: (I) a review of the literature regarding the concepts and applications of digital curation; (II) research and analysis of the publication and evaluation of Digital Educational Resources on Digital platforms and a (III) prospective research with teachers of Brazilian basic education. The study results in a proposal for digital curation created in a collective process and houses curation flows and criteria, for all the necessary steps in its process, considering the internal and external factors present in the Digital platforms, I understand the political scenario that governs society and the most varied contexts of users of these platforms.